Gedächtnisschrift für Peter Mankowski - von Bar, Christian; Magnus, Ulrich; Mansel, Heinz-Peter; Knöfel, Oliver L.; Wudarski, Arkadiusz (Mohr Siebeck, 2024)
To honour and pay tribute to Peter Mankowski and his remarkable academic legacy, this commemorative volume presents a vast collection of essays from home and abroad that match the breadth of the outstanding and prolific jurists main scholarly interests, which ranged from international private law to insolvency and civil procedure law, arbitration and uniform law (particularly UN sales law) as well as comparative law and legal culture research.
PublicationDate: 20240930
Keywords: Internationales Privatrecht -- Rechtsvergleichung -- Rechtskultur -- Internationales Zivilverfahrensrecht -- Internationales Insolvenzrecht -- COMI -- apokryphe Apostelakten -- New Yorker Übereinkommen Schiedsgerichtsbarkeit -- Schiedsrecht -- Einheitsrecht (insbesondere UN-Kaufrecht) -- "Zoo« der Gesellschaftsformen -- gesellschaftsrechtliche Erfinder und Wegbereiter -- nationaler und internationaler Rechtsformenwettbewerb -- Festschriften -- Allgemeines -- Bürgerliches Recht -- Zivilverfahrensrecht, Insolvenzrecht -- Europarecht -- Ausländisches Recht, Rechtsvergleichung